Heterogeneity of Astrocytic and Neuronal GLT-1 at Cortical Excitatory Synapses, as Revealed by its Colocalization With Na+/K+-ATPase α Isoforms. (27th September 2018) - Melone, Marcello; Ciriachi, Chiara; Pietrobon, Daniela; Conti, Fiorenzo
Abstract: GLT-1, the major glutamate transporter, is expressed at perisynaptic astrocytic processes (PAP) and axon terminals (AxT). GLT-1 is coupled to Na + /K + -ATPase (NKA) α1–3 isoforms, whose subcellular distribution and spatial organization in relationship to GLT-1 are largely unknown. Using several microscopy techniques, we showed that at excitatory synapses α1 and α3 are exclusively neuronal (mainly in dendrites and in some AxT), while α2 is predominantly astrocytic. GLT-1 displayed a differential colocalization with α1–3. GLT-1/α2 and GLT-1/α3 colocalization was higher in GLT-1 positive puncta partially (for GLT-1/α2) or almost totally (for GLT-1/α3) overlapping with VGLUT1 positive terminals than in nonoverlapping ones. GLT-1 colocalized with α2 at PAP, and with α1 and α3 at AxT. GLT-1 and α2 gold particles were ∼1.5–2 times closer than GLT-1/α1 and GLT-1/α3 particles. GLT-1/α2 complexes (edge to edge interdistance of gold particles ≤50 nm) concentrated at the perisynaptic region of PAP membranes, whereas neuronal GLT-1/α1 and GLT-1/α3 complexes were fewer and more uniformly distributed in AxT. These data unveil different composition of GLT-1 and α subunits complexes in the glial and neuronal domains of excitatory synapses. The spatial organization of GLT-1/α1–3 complexes suggests that GLT-1/NKA interaction is more efficient in astrocytes than in neurons, further supporting the dominant role of astrocytic GLT-1 in glutamate homeostasis.